Carreira e trabalho na vida após o doutorado : uma análise psicossocial das trajetórias de psicólogos doutores - Fabrício Aparecido Bueno (2023)
This study abridges the results of a research which aims to analyze the trajectories taken by psychologists who graduated from the program of PhD in Psychology at the Federal University of Minas Gerais (UFMG), in order to understand, from a psychosocial perspective, the impacts of the PhD on their careers. The theoretical framework that guided the lines of the research, both regarding the underlying conception of a career construction as well as the relation of the investigative trend facing the phenomenon of socio-professional trajectories, was the career psychosocial approach proposed by Marcelo Afonso Ribeiro.The research contains two stages, the first bears a theoretical-critical nature while the second holds an empirical trend. In the first stage, it was stablished the foundations of a psychosocial approach to investigate higher education graduates’ trajectories. Departing from a critical analysis of Brazilian literature on researches focused on graduates of higher education courses, it was possible to detect the theoretical fragility of studies approaching this topic in Brazil. It was also possible to identify the lack of a consistent dialogue between these works and concepts and problems originating from other more epistemologically consolidated fields of investigation. In order to display a proposal to overcome this gap, it was brought into light, by the production of a theoretical essay, the advantages that the adoption of a psychosocial framework on the notions of careers provides to investigations aiming to understand the dimension of constructions of subjects’ life trajectories after finishing the academic training. The second stage of the research consisted of applying the precepts elaborated in the initial phase and it was composed of a qualitative research based on interviews with 14 graduates of the PhD in Psychology at UFMG, graduated between 2012 and 2018. In general, the interviews focused on encouraging graduates to produce narratives about their professional trajectories before, during and after finishing the doctorate program, and to reflect on the impacts of doctoral training on the ways these trajectories were built. The thesis presented here is based on three articles generated as a result of the development of the two stages of the research. The first article comes from the theoretical-critical phase and the two subsequent articles from the empirical work. The contributions of this thesis to the literature that deals about the themes it focuses on must be considered in the light of the contributions provided by each of the three articles (studies) that build it up. The first article provides a guiding framework for the production of studies with graduates of higher education, both undergraduate and postgraduate (stricto and latu sensu), from a focus centered on the graduates' own perception of their trajectories, something sparsely explored in literature produced in Brazil. The second article analyzes the issue of career decisions after the doctorate, highlighting how the recent reconfigurations of the academic job market have had profound impacts on the relationship between doctors and their professional and life projects. The third article, finally, dialogues with the discussions about the impacts of postgraduate training on the lives of stricto-sensu postgraduates, involving both, those who choose to continue their professional activities in the academic area and those who follow a trajectory of total or partial insertion outside the academy.